A novel 110 kV power line inspection robot and its climbing ability analysis. (30th May 2017) - Yue, Xiang; Wang, Hongguang; Jiang, Yong
A novel mechanism for 110 kV power transmission line inspection is presented according to the requirements of inspection tasks and characteristics of obstacles on power transmission lines. Its configuration is introduced, and the navigation process of typical obstacles is planned. Then the kinematics equations and the workspace are derived. The grade ability of the power transmission line inspection robot is analysed and then improved by some measures. The quasi-static mode of the robot and the contact mechanics of the wheels are established. Adhesion force of the driving wheel can be improved by optimizing the structure of the wheel and the wheel load is reasonably distributed by planning the posture of the robot. So the climbing ability is ameliorated. The climbing ability of the different wheel structure and the different posture is simulated. Furthermore, the simulation of the navigation of the strain clamp and test of navigation of the jumper in the laboratory have been carried out. The simulation results demonstrate that the mechanism has such characteristics as compact construction, strong stability and excellent obstacle negotiation capability.